KARAKTER PANCA PANDAWA DALAM EPOS MAHABARATA SEBAGAI PEDOMAN MENJADI PENYULUH AGAMA HINDU YANG BERKARAKTER - Gede Agus Jaya Negara (Maha Widya Duta : Jurnal Penerangan Agama, Pariwisata Budaya, dan Ilmu Komunikasi, 2022)
The existence of different views or beliefs will be difficult to avoid friction or conflict. Conflict of belief is a dynamic that occurs in people's lives in Indonesia. Religious instructors are very risky and important jobs in improving the quality of religious life in accordance with their beliefs and beliefs as well as increasing religious harmony in their respective fostered areas so that no more problems arise due to differences in views based on religion. An instructor must have a good character like the character of the Panca Pandavas in the Mahabharata epic, this character can be guided by Hindu religious instructors in carrying out their duties and functions. The epic Mahabharata is one of the stories contained in Itihasa about the journey of the Kuru people with the core story being in the conflict between the Panca Pandavas and the Kauravas. The Panca Pandavas themselves are children born from the incarnation of the gods with almost perfect characteristics. It is this trait that must be imitated by Hindu religious educators in order to become instructors who have characters such as wise characters, firm in their views, honest, brave, loyal, gentle, polite, patient, confident, obedient, steadfast, smart and thorough.